Pressure-induced metallization and robust superconductivity in pristine 1T-HfSe2. (July 2022) - Rahman, S.; Saqib, H.; Liang, X.; Errandonea, D.; Resta, A.S.; Molina-Sanchez, A.; Gao, G.; Wang, L.; Tian, Y.; Mao, H-K.
Abstract: The two-dimensional semiconductor 1T-HfSe2 is found to have highly tunable transport properties under pressure including metallization and pressure-driven superconductivity. The temperature-dependent resistivity of the sample suggests that a charge-density wave (CDW) state exists at low pressures in HfSe2, but it is suppressed below 20 GPa. It is further found that metallization takes place at ∼24 GPa followed by the appearance of a superconducting state at 26 GPa with a T c of 6.7 K. Upon further compression to 33 GPa, the T c increases monotonically to 7.5 K. Raman spectra, x-ray diffraction, transport measurements, and density-functional theory calculations suggest that the occurrence of the pressure-induced metallization and superconducting transition are intimately linked to a structural phase transition from the trigonal (P 3 ‾ m1) to a hexagonal structure ( P 63 / mmc ). Because of the phase transition, a massive structural reconstruction, and substantial band-structure changes around the Fermi level take place, which are due to the modification of weak van der Waals forces. The pressure-induced manipulation of the transport properties of 1T-HfSe2 could provide crucial information towards its practical applications. Graphical abstract: Image 1 Highlights: 1 T -HfSe2 is found to have highly tunable transport properties under pressure including metallization and superconductivity. A charge-density wave state is found to exist at low pressures in HfSe2 below 20 GPa. The metallization takes place at ∼24 GPa followed by the bulk superconductivity with a T c of 6.7 K at 26 GPa. The metallization and superconducting transition are linked to a phase transition from the trigonal to a hexagonal structure.